(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article thoroughly investigates the role of prosodic units in the pragmatic organization of spoken Uzbek, asserting that prosodic segmentation functions as a fundamental, systematic mechanism for encoding pragmatic meaning, rather than merely being a byproduct of syntactic structure. This study employs a carefully curated corpus of approximately 90 minutes of spoken Uzbek, comprising both natural conversational dyads and formal radio broadcasts. It utilizes a multi-layered annotation framework grounded in the theory of Intonation Units (IUs) as formulated by Chafe (1) and further developed within interactional linguistics (2). The analysis systematically examines the relationship between prosodic boundaries—defined by the convergence of pauses, pitch resets, and final syllable lengthening—and three essential pragmatic functions: topic management, information focus (particularly contrastive focus), and the expression of speaker stance. The findings indicate that grammatical structure provides a fundamental framework for speech production; however, the dynamic alteration of prosodic features serves as the primary mechanism through which speakers structure discourse, convey the status of referents in common ground, and express their subjective orientation towards propositional content. The segmentation of speech into prosodic units is demonstrated to be a rule-based framework wherein pragmatic functions requiring heightened salience or autonomous processing are intentionally assigned distinct prosodic units. This study improves pragmatics, prosody, and discourse analysis by looking at a universal cognitive process in a specific language. This has big effects on theoretical frameworks for the grammar-pragmatics interface, cross-linguistic typology, and natural language processing applications for Turkic languages.